Early detection of immune checkpoint inhibitor-related subclinical cardiotoxicity: A pilot study by using speckle tracking imaging and three-dimensional echocardiography - Xu, Aiqing; Yuan, Ming; Zhan, Xiaoping; Zhao, Gangjian; Mu, Guanyu; Wang, Tingting; Hu, Hailong; Fu, Huaying (Frontiers in Cardiovascular Medicine, 2022)
Background Early detection of subclinical cardiotoxicity of immune checkpoint inhibitor (ICI) therapy can be challenging. Objective To evaluate subclinical cardiac dysfunction using two-dimensional speckle tracking imaging (2D-STI) and three-dimensional echocardiography in Chinese patients. Methods Fifty-five consecutive patients with malignant tumors treated by immunotherapy were included. They were examined by echocardiography before immunotherapy and after immunotherapy. Left ventricular ejection fraction (LVEF) was calculated in three-dimensional imaging. Moreover, left ventricular global longitudinal peak systolic strain (LVGLS), left ventricular global circumferential peak systolic strain (LVGCS), right ventricular global longitudinal systolic strain (RVGLS), right ventricular free wall longitudinal peak systolic strain (RVFWLS), and tricuspid annular plane systolic excursion (TAPSE) were evaluated. Clinical and laboratory parameters were recorded. Cardiac toxicity events were defined as the presence of heart failure symptoms, LVEF reduction, and increase in troponin. Subclinical cardiac toxicity was defined as cardiac dysfunction associated with ICI treatment, with absent or delayed ICI-associated cardiotoxicity clinical symptoms. Results Compared with baseline, the LVGLS, TAPSE, and RVGLS significantly deteriorated after ICI treatment [(–18.63 ± 2.53)% vs. (–17.35 ± 2.58)%, P = 0.000; 18.29 ± 6.23 vs. 14.57 ± 3.81, P = 0.0001; and (–18.45 ± 4.65)% vs. (–14.98 ± 3.85)%, P = 0.0001, respectively]. LVGLS (–17.35 ± 2.58, P = 0.000), TAPSE (14.57 ± 3.81, P = 0.0001), and RVGLS [(–14.98 ± 3.85)%, P = 0.0001] were decreased after ICI immunotherapy. Kaplan-Meier curve analysis showed that LVGLS was more sensitive than the cardiac toxicity events to assess ICI-related subclinical cardiac dysfunction (log-rank P = 0.205). The ROC curve showed that the cutoff value of ΔLVGLS was -13%. Conclusion Subclinical cardiac dysfunction can be detected using two-dimensional speckle-tracking imaging. LVGLS, RVGLS, and TAPSE are more sensitive indices for detection. Clinical trial registration [https://www.chictr.org.cn/showprojen.aspx?proj=27498], identifier [ChiCTR1800016216].